2020
DOI: 10.1515/jbcpp-2019-0220
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological, anticholinesterase, antilipidemic, antidiabetic and antioxidant potentials of Grewia optiva Drummond ex Burret extracts

Abstract: BackgroundIn this study, Grewia optiva Drummond ex Burret root extracts were assessed for use as a remedy for oxidative stress, diabetes mellitus and neurological disorders.MethodsThe antioxidative potentials of the extracts were determined using DPPH and ABTS assays, whereas their enzyme inhibitory potentials were determined against acetylcholinesterase (AChE), butyrylcholinesterase (BChE), α-glucosidase and α-amylase. In the in vivo experiments, methanol extract was orally administered to mice (n = 5) at fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…In addition, the onset of few neurodegenerative diseases was involved with AChE enzyme. 7 Chronic exposure of naringin (25 mg/kg) produces a minimal effect on the performance of rats in the redial and water maze tasks; while in large dose (100 mg/kg) formed its maximum responses. The cholinergic system plays an active role in several physiological processes like learning, memory and synaptic plasticity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the onset of few neurodegenerative diseases was involved with AChE enzyme. 7 Chronic exposure of naringin (25 mg/kg) produces a minimal effect on the performance of rats in the redial and water maze tasks; while in large dose (100 mg/kg) formed its maximum responses. The cholinergic system plays an active role in several physiological processes like learning, memory and synaptic plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…The superoxide semi-reduced radical ions formed due to Al intoxication can cause cognitive deficiency and dementia in the brain, 5 suggesting the influence of Al and superoxide radical interactions in the promotion of superoxide associated biological oxidation. 6,7 Furthermore, the exposure of Al can result in its CNS accumulation and induces the reactive oxygen species (ROS) formation. This results in increased lipid peroxidation and altering the brain oxidative mechanisms that might promote β-amyloid peptide deposition and formation.…”
Section: Introductionmentioning
confidence: 99%
“…Hiba et al have reported the isolation of octanoic acid, tridecanoic acid, octadecatrienoic acid, and eicosanoic acid from Grewia tenax [ 6 ]. Additionally, previously, we evaluated the Grewia optiva extracts for different biological potentials and isolated eight compounds from this plant [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The search for natural antioxidants present in medicinal plants is very important due to their potential for extensive use in practical applications [ 17 , 18 , 19 , 20 , 21 ]. Additionally, natural compounds have been found to be promising in treating some neurodegenerative diseases [ 9 ]. For instance, two clinically approved drugs for the treatment of Alzheimer’s disease (AD), i.e., rivastigmine and galantamine, are derived from plant sources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation